Offenders with learning disabilities: the involvement & attitudes of professionals - Cant, Richard (2002)
It has been reported that there is an over-representation of people with learning disabilities in prison populations. Various explanations have been offered for this including theories that people with disabilities are susceptible to criminal behaviour, and that they receive different treatment within the justice system. There is no evidence of over-representation of people with learning disabilities in the UK penal system although evidence does suggest that there are a significant number of prisoners with borderline learning disabilities who are psychologically vulnerable. This research set out to examine current levels of contact that psychiatrists have with various criminal justice agencies, as well as exploring the attitudes and beliefs of other criminal justice workers in order to assess current arrangements of treatment and care for offenders who have a learning disability.